Exploring Professional Support Offered by Midwives during Labour: An Observation and Interview Study - Stina Thorstensson; Anette Ekström; Ingela Lundgren; Elisabeth Hertfelt Wahn (Nursing Research and Practice)
Support in labour has an impact on the childbirth experience as well as on childbirth outcomes. Both social and professional support is needed. The aim of this study was to explore professional support offered by midwives during labour in relation to the supportive needs of the childbearing woman and her partner. The study used a qualitative, inductive design using triangulation, with observation followed by interviews. Seven midwives were observed when caring for seven women/couples in labour. After the observations, individual interviews with midwives, women, and their partners were conducted. Data were analysed using hermeneutical text interpretation. The results are presented with three themes. (1) Support as a professional task seems unclear and less well defined than medical controls. (2) Midwives and parents express somewhat different supportive ideas about how to create a sense of security. (3) Partner and midwife interact in support of the childbearing woman. The main interpretation shows that midwives' supportive role during labour could be understood as them mainly adopting the “with institution” ideology in contrast to the “with woman” ideology. This may increase the risk of childbearing women and their partners perceiving lack of support during labour. There is a need to increase efficiency by providing support for professionals to adopt the “with woman” ideology.